Direction of Trade Statistics Yearbook, 2018. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2018)
This paper discusses that shipments to and from free-trade zones and bonded warehouses, exclusion of military and other confidential items and government goods, value thresholds for customs registration of shipments, returned goods, and other goods missed by customs (or surveys) are examples of coverage differences that can result in inconsistencies. As a result of reporting and processing lags, trade data for a given period are often released before all customs documents for the period have been processed. These data are sometimes not revised, or, if data are revised, errors are nevertheless made in assigning the date on which goods are shipped or received and the late data are assigned to the wrong month, quarter, and/or year. Errors can also be made in assigning a destination to exports and an origin to imports during customs clearances, or in cases when the ultimate destination is changed after the initial consignment during transshipment, the change is not incorporated into published statistics via the release of revised data.